Effectiveness of learning complex motor activity and the model of manual dexterity in children aged 9-10 years - Matczak, Dawid; Wieczorek, Marta (Journal of Education, Health and Sport, 2022)
Introduction Learning is a complex and multi-dimensional process that depends on cognitive and emotional processes and the development of functional systems of the human body. One type of learning is motor learning. Its course and effects depend on many factors. One of the factors may be lateralization. Differences between intellectual and motor learning tend to be blurred when learning a complex motor activity takes place. Purpose The cognitive aim of the study is to assessment of the effectiveness (speed, efficiency, durability) of learning complex motor activity in relation to the selected aspect of physical development (the model of manual dexterity) of a selected group of girls and boys. Materials and methods: The study was conducted among 73 children (44 boys and 29 girls) aged 9 - 10 years. Authors used the pedagogical experiment method and the research tool was the program for learning how to juggle three tennis balls. To assess the selected aspects of physical development we chose the direct categorized observation method. As research tools Authors used the Vienna Test System (VTS) Results: Most of the examined girls and boys were characterized by an established model of manualness.Subjects with a fixed model of manualness learned faster and more effectively than people with an undetermined model of manualness. The examined girls with a fixed model of manuality achieved more lasting learning outcomes than girls with an unspecified model. Such a relationship was not observed in the group of boys. Conclusions: Boys and girls who are characterized by a fixed model of handedness achieve a higher effectiveness of learning a complex motor activity.